19.2: Accurate and Fast Eye‐box Measurement for Near‐eye Display Based on Image Recognition Algorithm. (26th August 2021) - Song, Li; Pan, Jiangen; Li, Qian; Pan, Minmin
Abstract : The measurement of eye‐box is very important for near‐eye display. This paper introduces a fast and accurate measurement scheme based on image recognition algorithm by a automatic robot measuring system. The influence of tilt angle and focus sharpness on eye‐box measurement is also analyzed